Occurrence and distribution of old and new halogenated flame retardants in mosses and lichens from the South Shetland Islands, Antarctica. (April 2018) - Kim, Jun-Tae; Choi, Yun-Jeong; Barghi, Mandana; Yoon, Young-Jun; Kim, Jeong-Hoon; Kim, Ji Hee; Chang, Yoon-Seok
Abstract: The spatial distribution of old and new halogenated flame retardants (HFRs), including polybrominated diphenyl ethers (PBDEs), hexabromocyclododecanes (HBCDs), and Dechlorane Plus (DPs) and related compounds (Dechloranes), were investigated in the South Shetland Islands of Antarctica, employing mosses ( Andreaea depressinervis and Sanionia uncinata ) and lichens ( Himantormia lugubris and Usnea antarctica ) as bioindicators. The levels of PBDEs, HBCDs, and Dechloranes ranged from 3.2 to 71.5, 0.63–960, and 2.04–2400 pg/g dw (dry weight) in the mosses, and from 1.5 to 188, 0.1–21.1, and 1.0–83.8 pg/g dw in the lichens, respectively. HFRs were detected in all of the collected samples, even in those from the remote regions. The dominance of high brominated-BDE, anti- DP fraction, and HBCD diastereomeric ratio in the samples from remote regions suggested the long-range atmospheric transport (LRAT) of the HFRs. The relatively high HBCDs and Dechloranes contamination and their similar chemical profile with commercial products in the vicinity of Antarctic research stations indicated that human activities might act as local sources, while PBDEs appeared to be more influenced by LRAT and bioaccumulation rather than local emission. Lastly, the relatively high HFR levels and dominance of more brominated BDEs at the Narębski Point and in the wet lowlands suggested that penguin colonies and melting glacier water could be secondary HFR sources in Antarctica. The HFR levels differed by sample species, suggesting that further research on the factors associated with the HFR accumulation in the different species is necessary. This study firstly reports the alternative HFR levels in a wide area of the Antarctica, which could improve our understanding of the source, transport, and fate of the HFRs. Graphical abstract: Image 1 Highlights: HFRs were detected in mosses and lichens from the South Shetland Islands. The main sources of HFRs were long-range atmospheric transport and human activities. The alternative HFRs seemed to be more affected by human activities than PBDEs. The HFR levels differed by species of the mosses and the lichens. Abstract : The old and new halogenated flame retardants, PBDEs, HBCDs, and Dechloranes, were detected in the remote region of Antarctica and their distribution and potential source were investigated.